Views from the inside: An appraisal of the effectiveness of international NGOs as agents of development through a case study of Concern Universal's Local Development Support Programme in Dedza District, Malawi - Mussa, Khadija Sungeni (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
Malawi, which became independent in 1964, attracted Non-Governmental Organisations (NGOs) from the early 1980s. Initially, NGO involvement was a response to the influx of refugees from neighbouring war-torn Mozambique. Since then, NGOs have been active in the development sector. Malawi, a small country, has widespread poverty, and has recently been in international headlines as a victim of floods, drought and food shortages. Economically unstable, with environmental problems, Malawi is in need of development assistance. NGOs have been centrally positioned in such efforts, but the academic literature on their role has been limited. NGO interventions in development efforts, generally, have been subject to controversy. While some argue that NGOs provide an essential means of development, especially where state capacity is limited, others argue that, with most NGOs headquartered or funded from abroad, their strategies and practices are often more accountable to external pressures than local needs. This thesis intervenes in these debates with a case study: with the aim of examining the sustainability, appropriateness, accountability and effectiveness of NGO projects, it looks at a project by the international NGO (INGO), Concern Universal (CU), which works in the central region in Dedza, Malawi. It examines the project, using fieldwork in three villages, looking at issues such as its use of participatory methods, relations with local government and village structures, capacity building methods, and donor relations. The thesis argues that (I)NGOs like CU exist in a conflicted situation: they have to remain in the good books of their donors, while, at the same time, maintaining accountability to their beneficiaries; they depend on their ability to manoeuvre through the conflict in order to ensure their continuity, and so, their impact is shaped by competing imperatives. CU has made a real impact on poverty alleviation efforts, but its methods and approaches are shaped by said competing imperatives.
Keywords: Uncatalogued